Why does the Mexican peso depreciate against the dollar? The role of productivity differentials - Arnoldo López Marmolejo; Daniel Ventosa-Santaulària (Inter-American Development Bank (IDB), 2018)
Over the last three decades, Mexico's macroeconomic policy has been driven by a sound orthodox strategy: an open economy via many trade agreements signed since the mid-1980s, a nominal exchange rate under a flexible regime since 1994, central bank autonomy, and responsible fiscal policy, among other benchmarks. Nevertheless, the exchange rate has continued on a path of depreciation against the US dollar. In this paper, we show that although an equilibrium relationship exists between the exchange rate and prices in Mexico and the US (its main commercial partner), there are other forces affecting the former. The main factor in this relentless long-term depreciation is the loss of productivity in Mexico relative to the US. In addition, we show that the extraordinary liquidity supplied by the US during the 2008 crisis caused the Mexican peso to appreciate against the dollar.
Keywords: C13; C22; E24; O11; O19; O47; 330; Nominal Exchange Rate; Productivity; Federal Reserve Assets; Prices